Prediksi Perubahan Penggunaan Lahan Berbasis Cellular Automata Di Kota Batam Tahun 2041 - Yohanes Paulus Goo Ado; Rieneke L. E. Sela; Fela Warouw (JURNAL BIOS LOGOS, 2023)
Batam City is one of the industrial cities that is quite attractive to investors. The publication of the Batam City Concession Agency shows that there are 1,309 leading industries with a total of 169,000 workers. This affects the increase in population and changes in land use. This study aims to analyze the driving and inhibiting factors of land use change and predict land use, especially settlements in Batam City in 2041 using the cellular automata method. Factors driving land use change are proximity to industrial areas, existing settlements, trade and service areas, office areas, transportation facilities, health facilities, and arterial roads. Weighting using AHP shows the biggest weight on the existing settlement factor. Factors inhibiting changes in land use consist of protected mangrove forests, as well as areas whose existence needs to be maintained such as airport/port areas, industrial areas, trade and services, and offices. Predictions show that settlement land has grown to 15,872 hectares, open land has decreased by 1,366 hectares, agriculture has decreased by 1,195 hectares, forests have decreased by 656 hectares.